Fluid-based spectrally selective filters for direct immersed PVT solar systems in building applications. (August 2018) - Chemisana, D.; Fernandez, E.F.; Riverola, A.; Moreno, A.
Abstract: Liquid filters applied in hybrid photovoltaic-thermal (PVT) solar systems report potential benefits as they allow for selecting the wavelengths at which the solar cell operates with higher efficiency. Among the rest, low frequency photons are absorbed by the liquid, therefore not warming the cell up. In addition, direct immersion of photovoltaic cells in liquids enhances temperature control by cooling the cells under almost negligible contact resistance between the liquid and the cell. The characteristics of the liquids for direct immersed PVT application are described, defining an indicator (ideal filter window) to select the best liquid depending on the PV technology and the incident irradiance. Several liquids are assessed based on the required properties for the present application. As a conclusion, regarding optical, thermal, electrical and operational aspects, a mixture of deionized water and isopropyl alcohol results as proper candidate satisfying well all of them. Highlights: Key characteristics of liquid-based filters for direct immersed PVT are stated. Ideal Filter Window (IFW) criteria for PVT immersion liquids are defined. Optical, electrical and thermal properties of dielectric liquids are studied. Optical and electrical performance experiments are conducted. Mixtures of deionized water with IPA and DMSO result as better candidates.